KELAYAKAN MEDIA FLASH CARDDALAM SUBMATERI ZAT MAKANAN KELAS XI SMA - Gola, Lisa; Candramila, Wolly; Marlina, Reni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis Study Aimed To Determine The Feasibility Of Flash Card As A Medium In The Sub-Material Of Food Substance In Second Grade Of Senior High School.Descriptive Research Using Servey Methods With Purposive Sampling Teachnique. Descriptive Research In This Study Is Testing The Feasibility Of Flash Card As A Medium Of Learning In The Substance Substance Of Class XI Hight School. This Research Was Conducted In June-July 2017 By Making Flash Card Medium At The Biology Education Laboratory Of FKIP Tanjungpura University.The Media Validator Consisted Of 5 Validators, Namely 2 Lecture And 3 Teachers, 2 Expert Lecturers Determined From The Biologi Education Study Program At The Teaching And Education Faculty Of Tanjungpura University, The Criteria For Lecturers As Validators Namely Lecturers Who Were Experts In Instrument Validation And Media Validators, And Understand The Purpose And Step In Making Flash Card. Media Validators Consisted Of 5 People, Namely 2 Lecturers From Biology Education Study Program, Faculty Of Teacher Training And Education, University Of Tanjungpura And 3 Teachers From SMAN 1 Sengahtemila, SMAN 1 Sungai Raya, And SMA SantunUntan Respectively.The validity test of flashcards by 5 validators resulted in a CVI score of 0.87 and was categorized invalid so that it was not feasible to be used as a learning medium in thesub-material of Food Substance in the second grade of senior high school.                                                                                Keywords: Feasibility, Flash Cards, Food Substances